Peranan Anggaran Biaya Produksi Sebagai Alat Pengendalian Biaya Produksi Pada PT Yudhistira Ghalia Indonesia - Bogor - Septiani, Septiani; Herawati, Heti (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
Budgeting of production costs is very useful as a tool to find out and predict the costs of production process in order that any surplus or deficiency of the production components can be avoided. As a result, carrying out performance measurement for cost control becomes more simple and eventually the goal is achieved. The purpose of this study is to determine the role of the production cost budget as a means of controlling production costs. The data used in this research are gained from the interviews with relevant authorities and direct observation to record the budget and the realization of production costs in 2018 and 2019. Analysis of the difference in costs is conducted at PT Yudhistira Ghalia Indonesia using qualitative methods. The results of the research is obtained by comparing the budgeted costs with costs realization. The control of production costs can be done optimally. However, the company does not have factory’s overhead costs budget that distinguishes between fixed overhead costs with variables. It is also found out that there are deviations in direct labor costs resulting from the increased spending due to the hiring of new employees. Key words : Production Cost Budget and Cost Control